Hydropedological Interpretation of Regional Soil Information to Conceptualize Groundwater–Surface Water Interactions - van Tol, J.J. (2020)
The dominant soil distribution patterns in the catchments were then determined. Significant positive Spearman correlation coefficients exist between BFI and soil attributes such as depth (0.72), clay content (0.54), and the area covered by Recharge soils (0.81). The occurrence of Interflow and shallow soils is inversely correlated to BFI (−0.86 and −0.67, respectively), whereas CVB was positively correlated to the area of Interflow soils (0.81) and negatively to the area of Recharge soils (−0.75). Based on the hydropedological soil distribution pattern, three conceptual models of groundwater–surface water interactions were constructed: (i) those where vertical drainage and recharge of groundwater in the upper slopes are dominant, with return flow to soil layers in lower‐lying positions, and soil and groundwater contribute to streamflow; (ii) those where vertical drainage through soils and recharge of groundwater is dominant in upper and lower lying landscape positions, there is no return flow to soils, and only groundwater contributes to streamflow; and (iii) those where lateral flow at the soil–bedrock interface is dominant throughout the catchment, limited recharge occurs, and the stream is fed through lateral flow from soils with limited contribution from groundwater.